Fabrication of hydrophilic silica coating varnish on pineapple peel fiber based biocomposite - Tarmizi, Zatil Izzah; Maski, Anisa Nasuha; Rasit Ali, Roshafima; Che Jusoh, Nurfatehah Wahyuny; Md Akim, Abdah; Eshak, Zolkapli; Md Noor, Sabariah; Ibrahim, Norazana (International Journal of Integrated Engineering, 2019)
In the last several years, the interest on hydrophobic and hydrophilic solid subtract was increased due to many applications in daily life, agriculture and industry. The continuous effort has been made to fabricate suitable material with more efficient fabrication method. In this research, physical blending method have been used by mixing four components of modifying agent with organic beeswax varnish at different weight percentage. Those modifying agents consists of decamethylcyclopentasiloxane (D5), Silica nanoparticles (R812S), Polydimethylsiloxane (BP-9400) and non-ionic surfactant (Triton X-100) were mixed in the mass ratio of 52:3:34:1. The modified varnish produced was coated on Pineapple peel fiber (PAPF) biocomposite and were characterized using Water Contact Angle (WCA) instrument, Fourier Transform Infrared (FTIR) and Scanning Electron Microscope (SEM). Based on the wettability index analysis; the value of water contact angle was reduced when increasing weight percent of modifying agents from 101.87 to 22.98Â°. The morphology of the surface was observed to have more silica nanoparticles, along with the increasing concentration of modifying agent. It also supported by FTIR which shows the presence of Si-O peak at 1030.88 cm-1. These results proved that the modifying agent and organic beeswax varnish had successfully produced hydrophilic coated on the PAPF surface.